Antiproliferative Effect and Apoptosis Induced in Human Cell Lines by Bruguiera gymnorhiza Barks Methanol Extract - Warsinah, .; Sismindari, .; Susidarti, Ratna Asmah (Indonesian Journal of Cancer Chemoprevention, 2011)
The Antiproliferative effects of methanol extract from Bruguiera gymnorhiza (B. gymnorhiza) barks were tested in vitro against three human cell lines: Hela, Raji and Myeloma cells. The extract was found to have antiproliferative effects against Hela, Raji and Myeloma cells with an IC50 value of 133, 504 and 384 µg/mL, respectively. The antiproliferative test was then performed on Hela, Raji,  and  Myeloma  cells.  Cytotoxicity  assay  of  the  extract  was  then  determined  using  MTT method.  There  were  some  indications  of  apoptosis,  such  DNA  fragmentation,  as  assessed  by acrydine orange- ethidium bromide staining. These results indicate that extract from B. gymnorhiza barks can induce apoptosis in human cell lines.Key words: Antiproliferative, Apoptosis, B. gymnorhiza